INTERNET SHOPPING AND ITS IMPACT ON CONSUMER BEHAVIOUR - Zheng, Fayu (2006)
The main goal of the paper is to obtain quantitative evidence describing the actuality of internet shopping in the case of the UK and China in order to explain the development of internet shopping and its impact on consumer behaviour. The paper builds on the relevant literature and at the same time examines consumer behaviour by questionnaires. Furthermore, the future development of internet shopping will be measured, and a deep comparison of consumer behaviour between these two countries is also analysed. To reach those objectives a co-integration analysis and quantitative research methods are used to identify all aspect of the internet shopping and impact on consumer behaviour. The data results obtained revealed in the paper support the research questions that including recent trends and various issues of in internet shopping, and principal factors for consumer behaviour.